Midwives’ and Obstetricians’ Experience of Place in Relation to Supporting Physiological Birth: A Hermeneutic Phenomenological Study - Mellor, Christine (Auckland University of Technology, 2021)
National and international evidence shows that ‘place’ influences birth outcomes, but evidence is limited as to ‘how’. In New Zealand, there are significant differences in the rates of spontaneous vaginal births by ‘place’, along with differences when benchmarking low risk primiparae birthing in hospital maternity units throughout the country. This hermeneutic phenomenological study seeks to develop further insight into ‘place’ in relation to physiological birth. The research question asked: how do midwives and obstetricians experience place in relation to supporting physiological birth? Participants consisted of nine midwives (employed and self-employed) and three obstetricians, all practising in the greater Auckland region in primary or hospital maternity facilities, or both. The findings show that ‘place’ is not neutral; it influences what practitioners are directed towards and attuned to, how they feel, their ‘position’ within ‘place’, what is easier to achieve, and this shapes their practise. ‘Place’ affects how the key tensions of protection, time, efficiency, and resources are perceived and negotiated. Findings show that ‘place’ influences how the relationship between normality and risk is ‘seen’, and how being appropriately-patient in relation to labour progress is safeguarded, particularly between primary and secondary maternity care. The findings of this research contribute to a deeper understanding of the barriers and enablers to supporting physiological birth within ‘place’. The recommendations include safeguarding greater openness to possibilities between primary and secondary maternity care; experienced midwives acting as consultants of ‘normal’; providing a separate midwifery-led birthing space for low-risk healthy women who have chosen to birth in the hospital setting; and the importance of student midwives and doctors having an understanding of physiological birthing playing out in primary birthing units and the woman’s home.
Keywords: Physiological birth; Experience of place; Midwives; Obstetricians